Maintenance and Reversibility of Paroxysmal Atrial Fibrillation in JDP2 Overexpressing Mice - Gerhild Euler; Jacqueline Heger; Marcel Rossol; Rainer Schulz; Mariana Parahuleva; Jens Kockskämper (Cells)
Heart-specific overexpression of transcriptional regulator JDP2 (jun dimerization protein 2) for 5 weeks provokes paroxysmal atrial fibrillation (AF) in mice. We now investigated whether AF and atrial remodeling will be reversible upon termination of JDP2 overexpression, and whether paroxysmal AF converts to permanent AF in the presence of maintained JDP2 overexpression. Cardiac-specific JDP2 overexpression for 5 weeks, resulting in paroxysmal AF, was either continued or repressed via a tet-off system for another 5 weeks. ECGs were recorded weekly. Thereafter, heart and lung weights, and atrial mRNA and protein expression were determined. Extending JDP2 overexpression did not aggravate the AF phenotype, still paroxysmal AF, prolongation of PQ intervals, and atrial hypertrophy were present. This phenotype was completely reversible upon cessation of JDP2 overexpression. A massive downregulation of connexin40 and calcium handling proteins, including SERCA2a, calsequestrin, and ryanodine receptor, was observed in atria after prolonged JDP2 overexpression. In conclusion, atrial remodeling and paroxysmal AF under JDP2 overexpression are not sufficient to maintain or aggravate AF in the absence of JDP2. The comparison of the two groups indicates that the downregulation of calcium proteins and connexins is an important factor in the maintenance of the disease.